Parental Beliefs and Knowledge, Children’s Home Language Experiences, and School Readiness: The Dual Language Perspective - Luo, Rufan; Song, Lulu; Villacis, Carla; Santiago-Bonilla, Gloria (Frontiers in Psychology, 2021)
Parental beliefs and knowledge about child development affect how they construct children’s home learning experiences, which in turn impact children’s developmental outcomes. A rapidly growing population of dual language learners (DLLs) highlights the need for a better understanding of parents’ beliefs and knowledge of dual language development and practices to support DLLs. The current study examined the dual language beliefs and knowledge of parents of Spanish-English preschool DLLs (n=32). We further asked how socioeconomic and sociocultural factors were associated with parental beliefs and knowledge, and how parental beliefs and knowledge related to DLLs’ home dual language experiences and school readiness skills as rated by their teachers. Results suggested both strengths and opportunities for growth in parental beliefs and knowledge. Moreover, parents from higher-SES backgrounds reported beliefs and knowledge that were more consistent with scientific evidence. Furthermore, parental beliefs and knowledge was positively related to relative Spanish input at home and negatively related to the frequency of English language and literacy activities. However, parental beliefs and knowledge were not associated with children’s dual language output at home or the frequency of Spanish language and literacy activities. Finally, parental beliefs and knowledge were associated with children’s school readiness skills in Spanish but not in English. Together, these findings highlight the need for culturally responsive interventions and parent education programs, which must recognize both the strengths and areas of improvement in parents of DLLs and support parents to transform knowledge into high-quality language and literacy experiences that benefit DLLs.